Intracellular Recording of Human Cardiac Action Potentials on Market-Available Multielectrode Array Platforms - Melle, Giovanni; Bruno, Giulia; Maccaferri, Nicolò; Iachetta, Giuseppina; Colistra, Nicolò; Barbaglia, Andrea; Dipalo, Michele; De Angelis, Francesco (Frontiers in Bioengineering and Biotechnology, 2020)
High quality attenuated intracellular action potentials from large cell networks can be recorded on multi-electrode arrays by means of 3D vertical nanopillars using electrical pulses. However, most of the techniques require complex 3D nanostructures that prevent the straightforward translation into marketable products and the wide adoption in the scientific community. Moreover, 3D nanostructures are often delicate objects that cannot sustain several harsh use/cleaning cycles. On the contrary, laser optoacoustic poration allows the recording of action potentials on planar nanoporous electrodes made of noble metals. However, these constraints of the electrode material and morphology may also hinder the full exploitation of this methodology. Here, we show that optoacoustic poration is also very effective for porating cells on a large family of MEA electrode configurations, including robust electrodes made of nanoporous titanium nitride or disordered fractal-like gold nanostructures. This enables the recording of high quality cardiac action potentials in combination with optoacoustic poration, providing thus attenuated intracellular recordings on various already commercial devices used by a significant part of the research and industrial communities.